Maternal Measles Antibodies and Their Influence on All-cause Mortality Following Measles Vaccination: An Alternative to Measure Very Low Maternal Antibody Levels. (16th October 2018) - Smits, Gaby; Stabell Benn, Christine; Whittle, Hilton; van Binnendijk, Rob; Aaby, Peter; van der Klis, Fiona
Abstract: It was previously shown by hemagglutination inhibition that measles vaccination in the presence of maternal measles antibodies was associated with reduced all-cause mortality. We confirmed this serological association using a multiplexed immunoassay as a sensitive alternative and estimated a threshold concentration (28.7 mIU/mL) that correlates with lower all-cause mortality ( P = .02).